A parametric study on design and characteristics of stepwise-built functionally graded Hydroxyapatite/Titanium - JAMALUDIN SITI NUR SAKINAH, . (2015)
Demand exists to enhance the performance and capability of engineering materials for various advanced engineering applications such as bioengineering, biomedical, aerospace and electronic devices. In order to fulfil the demand, concept of property gradation in functionally graded materials (FGMs) has been introduced and it allows the elimination of many limitations found in conventional materials.